2001
DOI: 10.1210/jcem.86.11.7983
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic-Androgenic Steroid Therapy in the Treatment of Chronic Diseases

Abstract: The purpose of this study was to review the preclinical and clinical literature relevant to the efficacy and safety of anabolic androgen steroid therapy for palliative treatment of severe weight loss associated with chronic diseases. Data sources were published literature identified from the Medline database from January 1966 to December 2000, bibliographic references, and textbooks. Reports from preclinical and clinical trials were selected. Study designs and results were extracted from trial reports. Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
175
0
10

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(194 citation statements)
references
References 94 publications
1
175
0
10
Order By: Relevance
“…No studies have yet specifically investigated the ability to induce or enhance muscle weight gain by nutritional modulation of protein synthesis or protein breakdown rates. Optimising protein intake and essential amino acid intake may stimulate protein synthesis per se, but also enhance efficacy of anabolic drugs [20] as well as physiological stimuli such as resistance exercise [21]. Protein requirements in COPD patients and many other chronic diseases are not well established.…”
Section: Protein Metabolismmentioning
confidence: 99%
“…No studies have yet specifically investigated the ability to induce or enhance muscle weight gain by nutritional modulation of protein synthesis or protein breakdown rates. Optimising protein intake and essential amino acid intake may stimulate protein synthesis per se, but also enhance efficacy of anabolic drugs [20] as well as physiological stimuli such as resistance exercise [21]. Protein requirements in COPD patients and many other chronic diseases are not well established.…”
Section: Protein Metabolismmentioning
confidence: 99%
“…As their name suggests, they have anabolic properties responsible for nitrogen retention, increase of muscular volume and strength. The androgenic properties are responsible for the development of the masculine sexual characteristics and for many of the collateral effects [1][2][3][4] . Although the AAS have many aims for the treatment/control of many diseases, such substances are being used in a nontherapeutic and indiscriminate manner in our society, with the purpose to improve sports performance and mainly esthetics [1][2][3]5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…The androgenic properties are responsible for the development of the masculine sexual characteristics and for many of the collateral effects [1][2][3][4] . Although the AAS have many aims for the treatment/control of many diseases, such substances are being used in a nontherapeutic and indiscriminate manner in our society, with the purpose to improve sports performance and mainly esthetics [1][2][3]5,6 . An investigation on the AAS use in the united States in the 1990's decade observed that about 1,000,000 of north Americans had already used such substances for non-therapeutic aims 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Nandrolone, or 19-nortestosterone, is an anabolic steroid initially introduced for the treatment of anemia, osteoporosis, and breast carcinoma (1,2 ). Nandrolone is available in several pharmaceutical formulations as a 17␤-hydroxy ester in an oily matrix or as a nandrolone salt (decanoate or sodium sulfate) in an aqueous solution.…”
mentioning
confidence: 99%